The Sumerian world
1 online resource (xxiv, 659 pages)
Keywords: 'The Sumerian World' explores the archaeology, history and art of southern Mesopotamia and its relationships with its neighbours from c.3,000 - 2,000BC. Including material hitherto unpublished from recent excavations, the articles are organized thematically using evidence from archaeology, texts, and the natural sciences.